Komik Digital Sebagai Mpeningkatan Awareness Mahasiswa Awareness Mahasiswa S1 Fakultas Kedokteran Gigi Universitas Airlangga Terhadap Pengaruh Karies Pada Status Gizi Anak - Ninuk Hariyani (Scholar Center, 2022)
ABSTRACT Dentists are often required to deal with dental health problems curatively but are lacking in providing health promotion programs which include the preventive aspects. Students in the Faculty of Dentistry need to be trained to increase their knowledge and awareness to provide more health promotion to the population. Dental health promotion requires sufficient knowledge and a high level of awareness, which must be understood by students who will later become health service providers to the wider community. The effect of caries on the nutritional status of children is one of the important themes that should be included in the theme of health promotion to the community. The method used in this community service is engagement method using a digital comic as a media. This comic is given to undergraduate students of the Faculty of Dentistry to increase their knowledge and awareness of the effect of caries on children's nutritional status. The results of the pre-test and post-test comparison showed that the digital comic about the effect of caries on children's nutritional status can be used to increase awareness of undergraduate students of the Faculty of Dentistry on this theme. Keynote: Student’s awareness, Digital comic, Caries, Nutrition ABSTRAK Dokter gigi sering dituntut untuk menangani permasalahan-permasalahan kesehatan gigi secara kuratif, akan tetapi kurang dalam pemberian promosi kesehatan yang termasuk segi preventif. Hal ini perlu dilatihkan sejak mereka menjalani pendidikan di Fakultas Kedokteran Gigi. Promosi kesehatan gigi memerlukan pengetahuan yang cukup serta tingkat awareness yang tinggi, yang harus dipahami oleh mahasiswa yang nantinya akan ikut menjadi pemberi layanan kesehatan pada masyarakat luas. Pengaruh karies pada status gizi anak merupakah salah satu tema penting yang seyogyanya masuk dalam tema promosi kesehatan kepada masyarakat. Metode pelaksanaan yang digunakan dalam pengabdian masyarakat ini dilakukan dengan menggunakan metode engagement menggunakan media komik digital yang diberikan kepada mahasiswa S1 Fakultas Kedokteran Gigi guna meningkatkan pengetahuan dan awareness mereka terhadap pengaruh karies pada status gizi anak. Hasil perbandingan pre-test dan post-test menunjukkan bahwa komik digital mengenai pengaruh karies pada status gizi anak ini dapat digunakan untuk meningkatkan awareness mahasiswa S1 Fakultas Kedokteran Gigi akan tema tersebut. Kata kunci: Student’s awareness, Komik digital, Karies, Gizi